Captain or deckhand? The impact of self-leadership on employees’ work role performance under remote work - Maden-Eyiusta, Ceyda; Alparslan, Suzan Ece (Frontiers in Psychology, 2022)
Relying on self-determination theory, we investigate the mediating role of psychological empowerment in the relationship between self-leadership and work role performance (task proficiency, task adaptivity, and task proactivity) in remote work settings. We also explore whether and how supervisor close monitoring moderates the indirect impact of self-leadership on work role performance. We tested our hypotheses using a two-study design including white-collar employees from a broad range of jobs and companies (Study 1) and employee-supervisor dyads working in small and medium-sized firms (Study 2) in Turkey. In Study 1, we found that self-leadership had a positive indirect effect on employees’ work role performance through psychological empowerment. In Study 2, the cross-lagged two-wave design confirmed this indirect effect and provided partial support for the moderating role of supervisor close monitoring. Our study contributes to research on self-leadership and work role performance by providing a detailed understanding of the motivational process through which self-leadership leads to increased work role performance. The study also offers practical insights for enhancing self-leaders’ work role performance, particularly within the remote work context.